Attack of the killer donuts [videorecording (DVD)] - Wagner, Rafael Diaz; Dechristopher, Chris; Dalton, Nathan; Ray, Justin; Compton, Kayla; England, Allison (Level 33 Entertainment, 2018)
A chemical accident in a sleepy town turns ordinary donuts into bloodthirsty monsters. Unaware of the donuts' danger, Johnny, Michelle and Howard sell them to unsuspecting costumers. When the donuts start eating their victims, the only way the three friends can save their sleepy town is to track down the Killer Donuts and destroy them. The final standoff is where it all began: Dandy Donuts.